2013
DOI: 10.1161/circep.112.975888
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Hemodynamic Support With Impella 2.5 During Scar-Related Ventricular Tachycardia Ablation (PERMIT 1)

Abstract: Background-Percutaneous left ventricular assist devices (pLVADs) are increasingly being used to facilitate ablation of unstable ventricular tachycardia (VT), but the safety profile and hemodynamic benefits of these devices have not been described in a systematic, prospective manner. Methods and Results-Twenty patients with scar VT underwent ablation with a pLVAD. Neuromonitoring using cerebral oximetry was performed to evaluate a cerebral desaturation threshold to guide the duration of activation/entrainment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 23 publications
3
69
0
Order By: Relevance
“…In a prospective evaluation of pLVADs, patients were maintained in VT for nearly 1 hour. 12 These findings are similar to those of other investigators. [11][12][13][14] Common to these studies is the finding that pLVAD use provided no evidence of benefit in terms of postablation inducibility or freedom from recurrent VT compared with ablation without pLVAD support, although fewer comorbidities were present in cases without pLVAD support.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a prospective evaluation of pLVADs, patients were maintained in VT for nearly 1 hour. 12 These findings are similar to those of other investigators. [11][12][13][14] Common to these studies is the finding that pLVAD use provided no evidence of benefit in terms of postablation inducibility or freedom from recurrent VT compared with ablation without pLVAD support, although fewer comorbidities were present in cases without pLVAD support.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3][4][5][6][7][8][9] To facilitate entrainment and activation mapping of hemodynamically unstable VT and mitigate the effects of frequent induction and prolonged VT duration on end-organ perfusion, several studies have demonstrated the feasibility of percutaneous left ventricular assist devices (pLVADs) for hemodynamic support during ablation procedures. [10][11][12][13][14] In these studies, pLVAD support resulted in increased mapping time during VT, less requirement for VT termination because of hemodynamic instability, and more VT terminations during ablation. However, there is limited data to ascertain whether this acute hemodynamic benefit translates into improved clinical outcomes.…”
mentioning
confidence: 93%
“…2). 30,31 Limitations apply when using these devices in VT ablation. The TandemHeart's transseptal placement precludes the same access for ablation catheters, so only the retrograde approach from the femoral artery is feasible.…”
Section: Use Of Mechanical Supportmentioning
confidence: 99%
“…In the adult population, patients with severe, nonoperable valve disease represent a rapidly growing population; carefully selected patients may benefit from cardiac support during percutaneous aortic valvuloplasty or aortic valve replacement [31,32]. Similarly, patients referred for electrophysiologic procedures with severe underling LV dysfunction may not tolerate sustained arrhythmias during prolonged electrophysiological mapping and ablation procedures [33,34]. Finally, patients with right ventricular (RV) failure are at considerably higher risk for morbidity and mortality when presenting with AMI, ADHF, or CS.…”
Section: Emerging Populationsmentioning
confidence: 99%